Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Terhadap Kemampuan Komunikasi Matematis Siswa Dan Sikap Positif Siswa - Hayatun Nufus; Muliana (Ar-Riyadhiyyat: Journal of Mathematics Education, 2021)
This study aims to determine the effect of the cooperative learning model type Group Investigation (GI) on student’s mathematical communication skills and attitudes positive students. this study uses a quantitative approach to this type of research quasi experimental design and using a posttest-only research design with nonequivalent groups. The data collection techniques used in this research is a test of mathematical communication skills and a positive attitude questionnaire test. Data analysis was conducted to test mathematical communication skills using t-test because the data is normally distributed and homogeneous, the data is processed using software SPSS 16. In accordance with the tasting criteria, namely if the value is sig. <0,05 then reject H0. From the results statistically significant Equal Variances Assumed is 0,00 less than 0,05 then, reject H0 and accept Ha. then for the questionnaire analysis of student’s positive attitudes using the t-test, the data of the questionnaire test results are transformed from ordinal to intervals with MSI help. The results showed that there was an influence on the learning model cooperative type Group Investigation (GI) on student’s mathematical communication skills and positive attitude of students.